Pengaruh GCG dan CSR Terhadap Nilai Perusahaan LQ45 Yang Terdaftar di BEI Tahun 2017-2020 - Puspita, Gita; Arisandy, Maya; Ichwanita, Aisyah (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
The purpose of this research was to determine : (1) the effect of board of directors on firm value, (2) the effect of independent board of commissioners on firm value, (3) the effect of corporate social responsibility on firm value, (4) the effect of good corporate governance and corporate social responsibility on firm value in LQ45 company listed in The Indonesian Stock Exchange on 2017-2020. This study used LQ 45 companies listed on the Indonesian Stock Exchange in 2017-2020. The method used in this research is a quantitative method with a total of 29 companies. The sample of this research was determined by purposive sampling so that 29 companies were obtained as sample. The results simultaneously showed that good corporate governance and corporate social responsibility have an effect on firm value. Furthermore, the partial test results showed that good corporate governance with the indicators of board of directors had an effect on firm value, the independent board of commissioners had an effect on firm value, and corporate social responsibility were not proven to have an effect on firm value. Keywords: good corporate governance, board of directors, independent board of commissioners, corporate social responsibility, firm value